¿“Nuevo” conflicto identificado?: El jabalí en establecimientos agropecuarios del noreste patagónico argentino - Viladrich, Leonel Jeremías (2025)
The wild boar is an invasive exotic mammal that impacts natural ecosystems and productive systems, although its effects on the latter have been little studied. In Argentina it is widely distributed and lacks natural predators, making hunting one of the main control strategies. This study was conducted in the semi-arid monte region, in northeastern Patagonia. The objective was to describe the impacts of wild boar and the control measures implemented in productive systems through semi-structured surveys conducted with livestock producers. The results highlight a direct impact, lamb predation and an indirect impact, illegal and informal hunting activities that affect producers. The main control measures identified include trapping, hunting with dogs, and night hunting with firearms and spotlights. This study provides key insights into the issue in the region and the role of producers in implementing control strategies.